Pengaruh Pengunaan Aplikasi Akuntansi Si-Apik, Ukuran Usaha dan Pendidikan terhadap Peningkatan Kinerja Keuangan UMKM Kabupaten Nganjuk - Indah Cahyaning Atie; Muhammad Ali Lutfi; Indrian Supheni (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
This activity is a research activity that aims to optimize the recording of financial transactions using the SI-APIK application belonging to Bank Indonesia. This research was conducted at SMEs in Nganjuk Regency. which aims to assist MSME Financial Performance in recording daily financial transactions and preparing financial reports that are accurate and in accordance with Small, Micro and Small Financial Accounting Standards as well as the influence of the size of the business and the education level of the business owner.